2018
DOI: 10.1093/occmed/kqy033
|View full text |Cite
|
Sign up to set email alerts
|

Age, burnout and physical and psychological work ability among nurses

Abstract: Findings indicated physical and psychological dimensions of work ability that differed by age and occupational burnout. This emphasizes the need for interventions to reduce burnout and to address age-related strengths and vulnerabilities relating to physical and psychological work ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 24 publications
8
42
1
4
Order By: Relevance
“…Our research shows that in men burnout is more probable to occur than in women. This corresponds to a previous research by Hatch et al concluding that there is lower burnout in females (38). However, LaFavet et al state that burnout criteria are met by more women (64.9%) than men (57.8%) (37).…”
Section: Discussionsupporting
confidence: 89%
“…Our research shows that in men burnout is more probable to occur than in women. This corresponds to a previous research by Hatch et al concluding that there is lower burnout in females (38). However, LaFavet et al state that burnout criteria are met by more women (64.9%) than men (57.8%) (37).…”
Section: Discussionsupporting
confidence: 89%
“…First, our study found that psychological fatigue and job satisfaction were all associated with chronic LBP, consistent with the findings of other studies37 38that showed that employees dissatisfied with their work were more prone to complain of back pain. High psychological fatigue could not only negatively affect one’s physical and mental work performance but also increase the possibility of medical errors and worker injuries 39–42. Second, our study found that occupational stressors, including high psychological job demand, low job control and low supervisor support, were independently associated with chronic LBP, consistent with the findings of other studies 43 44.…”
Section: Discussionsupporting
confidence: 89%
“…We could not confirm age and work duration could affect burnout, which is consistent with few other reports [19]. Other studies on the interaction of age and burnout and using a more comprehensive analysis showed that older age was associated with lower work capacity when high levels of burnout were present with the reverse association in lower levels of burnout in nurses [20]. This is indeed what we can somehow confirm with the association of FSS score with burnout scores in our doctors and nurses.…”
Section: Discussionsupporting
confidence: 48%